2022
DOI: 10.1007/s12033-022-00526-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Immune Infiltration Landscape and Identification of Prognostic Biomarkers for Esophageal Cancer

Abstract: Immunotherapy is an effective treatment for esophageal cancer (ESCA) patients. However, there are no dependable markers for predicting prognosis and immunotherapy responses in ESCA. Our study aims to explore immune gene prognostic models and markers in ESCA as well as predictors for immunotherapy. The expression profiles of ESCA were obtained from The Cancer Genome Atlas (TCGA), the Gene Expression Omnibus (GEO), and International Cancer Genome Consortium (ICGC) databases. Cox regression analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Additionally, the expression of PD-L1 was highest in ICI gene cluster C. Hence, the patients in ICI gene cluster C might have a better immune response. Te outcome of our analysis was in accordance with the previous study, which indicated that ICI clusters and ICI gene clusters in EC might infuence the expression of PD-L1 [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the expression of PD-L1 was highest in ICI gene cluster C. Hence, the patients in ICI gene cluster C might have a better immune response. Te outcome of our analysis was in accordance with the previous study, which indicated that ICI clusters and ICI gene clusters in EC might infuence the expression of PD-L1 [37].…”
Section: Discussionsupporting
confidence: 91%
“…The TGF- β /EMT signaling pathway influenced the expression of PD-L1 and promoted immune escape. All these results demonstrated that the ICI score was related to the PD-L1 but was not an independent prognosis marker for EC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity of the individual immunological milieu, quantifying the ICI models for individual malignancies is very relevant. In breast cancer, esophageal cancer, and the head and neck squamous cell carcinoma, the individualbased models based on tumor subtype-specific biomarkers have been well established to improve prognostic prediction [36][37][38]. In this study, we established an ICI score to quantify the ICI pattern.…”
Section: Discussionmentioning
confidence: 99%